La signoria rurale nell'Italia del tardo medioevo. 3 L'azione politica locale - Fiore, Alessio; Provero, Luigi (Reti Medievali E-Book, 2021)
Rural lordship is one of the classic medieval themes of recent decades, but its specific developments of the late Middle Ages have long been neglected by research, especially engaged in considering other processes in these centuries, such as the construction of regional states, the economic dynamics, the urban riots. This volume, as part of a large research project coordinated by Sandro Carocci, intends to help fill this gap by offering a wide sample of cases, relating to very different areas of the Italian peninsula. Local realities are investigated here from a very specific perspective, that is, in their strictly political dimension: while taking into account the broad contexts (economic, settlement and social) in which the rural lordships are located, the main questions of this volume focus on forms of the lordly domain and its relations with the subjects, with the regional states and with the other lordly powers.